"Hay que Cantar con Ternura": Baladas Románticas as a Site for Translingual Youth Convivencia. (November 2021) - de los Ríos, Cati V.; Portillo, Yared
For many Mexican-origin bi/multilingual children, Mexican music education begins early in their home. Music is inextricably linked with the sociocultural context in which it is produced, consumed, and taught and the interrelationship between music, society, and culture. Using ethnographic methods, this article examines a small group of bilingual and emergent bilingual Mexican-origin students who regularly congregated in their English teacher's classroom at lunchtime to recite and perform romance ballads, or what we refer to as baladas románticas, on a weekly basis. We use participant observation, plática-inspired interviews, focus groups, and video recordings to present ethnographic knowledge about how, for these young people, music was a way of being and a deliberate act to build community. Our findings describe the ways the bilingual students found themselves at the margins of their K–12 schooling experiences and, in turn, agentically fostered their own space for translingual expression and solace. This manifested in two primary ways: (a) how they collectively fostered their own form of convivencia (humanizing coexistence) anchored in their ancestral and cultural knowledge through their music-making and (b) how their music-making allowed them to release translingual and transmodal play and creativity that might have otherwise been suppressed at school. We end with a call for literacy researchers and educators to continue to recognize and honor students' lived translingual experiences, identities, and musical gifts as resources for learning.